2004
DOI: 10.1042/bj20031049
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of redox cell signalling: role of cysteine modification in controlling antioxidant defences in response to electrophilic lipid oxidation products

Abstract: The molecular mechanisms through which oxidized lipids and their electrophilic decomposition products mediate redox cell signalling is not well understood and may involve direct modification of signal-transduction proteins or the secondary production of reactive oxygen or nitrogen species in the cell. Critical in the adaptation of cells to oxidative stress, including exposure to subtoxic concentrations of oxidized lipids, is the transcriptional regulation of antioxidant enzymes, many of which are controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
471
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 527 publications
(496 citation statements)
references
References 57 publications
(86 reference statements)
18
471
3
4
Order By: Relevance
“…An alternative hypothesis of Nrf2 liberation, modification of Keap1, proposes that some reactive -SH groups on Keap1 act as oxidative stress sensors and that modification of them by ROS or electrophiles disrupts the Nrf2-Keap1 complex leading to Nrf2 dissociation. This hypothesis is supported by evidence of continuous Nrf2 activation by mutation of the active cysteine residues of Keap1 [67,70,71] and by the finding of conjugate formation between the electrophiles and the thiol group in Keap1 [72]. It seems that in the case of Nrf2 activation by HNE, Keap1 modification may be involved.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An alternative hypothesis of Nrf2 liberation, modification of Keap1, proposes that some reactive -SH groups on Keap1 act as oxidative stress sensors and that modification of them by ROS or electrophiles disrupts the Nrf2-Keap1 complex leading to Nrf2 dissociation. This hypothesis is supported by evidence of continuous Nrf2 activation by mutation of the active cysteine residues of Keap1 [67,70,71] and by the finding of conjugate formation between the electrophiles and the thiol group in Keap1 [72]. It seems that in the case of Nrf2 activation by HNE, Keap1 modification may be involved.…”
Section: Discussionmentioning
confidence: 85%
“…It seems that in the case of Nrf2 activation by HNE, Keap1 modification may be involved. Levonen et al found that HNE could conjugate with Keap1 in vivo, and the author proposed that this might be the underlying mechanism of HNE-mediated Nrf2 nuclear translocation [72]. Nonetheless, since HNE has been found to activate various signaling pathways including PKC [73][74][75][76][77][78][79], the possibility of Nrf2 phosphorylation by HNE-mediated signaling pathways cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,28 AREregulated gene transcription has been shown to be a central mechanism providing protection against oxidative stress in the cardiovascular system. [29][30][31] Oxidized low density lipoprotein and 15d-PGJ 2 , agents that are important in vascular inflammatory processes such as atherogenesis and are present in atherosclerotic lesions, 22,32 are also potent instigators of ARE activation, 17,33 suggesting that vascular inflammatory processes could be targets for ARE-regulated gene therapy. In addition, in I/R injury, activation of Nrf2 during reperfusion mediates cytoprotective gene expression, 34 implying that ARE-regulated vectors could also be used for attenuation of reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 It is also a potent inducer of Nrf2. 17,19 In HUVECs, the reporter gene expression of all constructs was increased by 15d-PGJ 2 ( Figure 2c). Similar to 293T cells, the basal luciferase activity was higher when the number of inserts was increased.…”
Section: Developing and Testing Of Oxidative Stress-inducible Plasmidmentioning
confidence: 93%
See 1 more Smart Citation